Tuning urine glucose sensing via metal films in graphene-oxide-based SPR architectures - Tene, Talia; Bellucci, Stefano; Guevara, Marco; Romero, Paul; Mayorga Pérez, Henry Sebastián; Gahramanli, Lala; Khankishiyeva, Rana; Sakher, Elfahem; Vacacela Gomez, Cristian (Frontiers in Nanotechnology, 2025)
In this work, we analyze graphene-oxide (GO)-based surface plasmon resonance (SPR) stacks of fixed architecture (SF6/metal/Si3N4/GO) at 633 nm to isolate the role of the plasmonic film (Au, Ag, Cu, and Al) in urine glucose (UGLU) sensing. Transfer-matrix simulations, validated against reference SPR data, identify the thickness windows for each layer and benchmark the angular response across a clinically relevant concentration ladder. Metals separate by function: Au yields the largest resonance-angle shifts and the highest sensitivity; Cu and Al provide the narrowest linewidths, elevating detection accuracy and quality factor; Ag offers a balanced compromise with deep minima. These trends persist over the examined UGLU range and clarify that maximizing sensitivity does not always maximize resolvability under fixed angular noise. We outline an experimentally feasible route—low-temperature Si3N4, nm-scale GO coatings and ultrathin dielectric caps for base metals—together with strategies to address urine-matrix effects and paths toward selective operation (e.g., enzyme or receptor layers). The results supply fabrication-ready prescriptions and a metal-dependent design map for urine-based SPR sensing, which is suitable for extension to multi-wavelength interrogation when dispersion data are available.